Coastal Tourism Attraction: Characteristics and Suitability of Management - Agus Agus; Muhammad Yahya; Darwis Darwis (Journal La Bisecoman, 2022)
The best solution in maximizing the utilization of the potential of coastal areas as a tourist attraction was a management system. This system can be regulated and controlled based on potential needs. Adjustment of the right concept from the concept that has been used so far needs to be done in coastal areas in South Sulawesi. Tanjung Bira Beach as a role model for the management of the coastal area of South Sulawesi where three sides are flanked by the sea, is an area that has the potential to develop coastal tourist attractions that are managed based on the methods, principles and capabilities of managers with the concept of sustainability and community based, becoming a foothold in the utilization of coastal potentials in an effective manner. optimally in order to provide tourist attraction products that are ready to be served to tourists. Qualitative research methods, with a case study approach. Primary data were obtained from interviews, field instruments and aerial photographs of the research locations, while secondary data were in the form of documentation and literacy. The results of the research show that the best method of managing coastal areas to become a superior tourist attraction product is: Establishing a management concept; utilization of coastal locations based on visitor needs; coastal ecological protection; maintain the physical environment of the coast; and the community as technical implementers of attraction management.